The effect of Zataria multiflora Boiss hydroalcoholic extract and fractions in pentylenetetrazole-induced kindling in mice - Shamsizadeh, Ali (Avicenna J Phytomed, 2016)
OBJECTIVE: At present, there are many antiepileptic drugs with a wide range of side effects on the human body. It was assumed that Zataria multiflora Boiss (Z. multiflora) with sedative, anti-spasmodic and anti-inflammatory activity may be effective in the treatment of epilepsy. The aim of the present study was to elucidate the effect of Z. multiflora hydroalcoholic extract and its fraction extracts on pentylenetetrazole (PTZ)-induced chemical kindling. MATERIALS AND METHODS: In this experimental study, eight separate groups of male albino mice were used. All groups received 11 separate intraperitoneal injections of PTZ (35 mg/kg) with two-day intervals. 30 min before the injection of PTZ, mice received vehicle, Z. multiflora hydroalcoholic extract (300 and 600 mg/kg), n-hexane, acetone, methanol fraction extracts (150 mg/kg), or diazepam (10 mg/kg). RESULTS: The kindled mice that were pretreated with vehicle showed a gradual increase in their seizure scores up to the end of the study. The hydroalcoholic extract of Z. multiflora (300 and 600 mg/kg) reduced seizure scores significantly. However, n-hexane, acetone and methanol extracts did not affect seizure scores significantly. CONCLUSION: The present findings demonstrate that the hydroalcoholic extract of Z. multiflora did reduce the severity of seizure attacks in PTZ-induced chemical kindling in mice.